Are social inequalities in acute myeloid leukemia survival explained by differences in treatment utilization? Results from a French longitudinal observational study among older patients - Eloïse Berger; Cyrille Delpierre; Fabien Despas; Sarah Bertoli; Emilie Bérard; Oriane Bombarde; Pierre Bories; Audrey Sarry; Guy Laurent; Christian Récher; Sébastien Lamy (BMC Cancer, 2019)
Abstract Background Evidences support social inequalities in cancer survival. Studies on hematological malignancies, and more specifically Acute Myeloid Leukemia (AML), are sparser. Our study assessed: 1/ the influence of patients’ socioeconomic position on survival, 2/ the role of treatment in this relationship, and 3/ the influence of patients’ socioeconomic position on treatment utilization. Methods This prospective multicenter study includes all patients aged 60 and older, newly diagnosed with AML, excluding promyelocytic subtypes, between 1st January 2009 to 31st December 2014 in the South-West of France. Data came from medical files. Patients’ socioeconomic position was measured by an ecological deprivation index, the European Deprivation Index. We studied first, patients’ socioeconomic position influence on overall survival (n = 592), second, on the use of intensive chemotherapy (n = 592), and third, on the use of low intensive treatment versus best supportive care among patients judged unfit for intensive chemotherapy (n = 405). Results We found an influence of patients’ socioeconomic position on survival (highest versus lowest position HRQ5: 1.39 [1.05;1.87] that was downsized to become no more significant after adjustment for AML ontogeny (HRQ5: 1.31[0.97;1.76] and cytogenetic prognosis HRQ5: 1.30[0.97;1.75]). The treatment was strongly associated with survival. A lower proportion of intensive chemotherapy was observed among patients with lowest socioeconomic position (ORQ5: 0.41[0.19;0.90]) which did not persist after adjustment for AML ontogeny (ORQ5: 0.59[0.25;1.40]). No such influence of patients’ socioeconomic position was found on the treatment allocation among patients judged unfit for intensive chemotherapy. Conclusions Finally, these results suggest an indirect influence of patients’ socioeconomic position on survival through AML initial presentation.